Effect Of Perforation Area On Temperature Distribution Of The Rectangular Fins Under Natural Convection - Ibrahim, Thamir K.; F., Basrawi; Marwah Noori, Mohammed; Hassan, Ibrahim (Asian Research Publishing Network (ARPN), 2016)
In many engineering applications extended surfaces known as fins, are used to enhance convective heat transfer. The problem of natural convection heat transfer for perforated fins was investigated in this work. An experimental study was conducted to investigate the natural convection heat transfer in a fin plate with circular perforations. The investigation is conducted to compare heat transfer rate of rectangular fins (15 fins) with a size of 100x270 mm embedded with circular vertical shaft. The patterns of perforations rectangular fins contain of 18 circular hole. The temperature distribution was examined for an array of rectangular fins. Experimental results show that the temperatures distribution along the nonperforated fin decreased from 49 to 42oC but for the perforated fin with hole diameter of 20mm, temperature decreased from 67 to 47.4oC with low power (200W). The temperature drop along the non-perforated fin decreased from 170 to 122oC but the temperature drop for perforated fin with hole diameter 20mm decreased from 170 to 101.7o C with high power (900W). Also, when the perforation diameter increased the decrement of the temperature between the base and tip of the fin was increases. Furthermore, when the perforation diameter increased, the heat transfer rate and the coefficient of heat transfer also increased